Comportamento reprodutivo de ovelhas crioulas lanadas com e sem cria ao pé - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The sheep farming becomes a profitable source to the producer, because with the genetic improvement, there are now animals of double and even triple aptitude. In order for this chain to become increasingly efficient, it is indispensable to obtain higher reproductive rates. The induction and synchronization of estrus for producers who work directly with sheep is a strategy for the animals to have better results in the pregnancy rate, synchronized births, facilitating the nutritional management of these animals. However, for a better understanding of reproduction as a whole, knowledge of behavior is essential to recognize the signals that the female demonstrates when she is able to receive intercourse. This work had the objective of studying the sexual behavior of Crioula Lanada females, with or without calves. The experiment was carried out at the Fazenda School of the Federal University of Pampa - UNIPAMPA / Campus of Dom Pedrito - RS, from February 1 to 24, 2019. Fifty-eight adult sheep were divided into two treatments: single sheep and lactating sheep, submitted to estrus synchronization through the application of two doses of 0.5 ml prostaglandin hormone, with a 10 day interval, the sheep remained from 08h to 20h with females, after that time the males were removed from the females to stay overnight. For the statistical analysis, a descriptive analysis was carried out to evaluate the data dispersion (Standard of R), where qualitative data such as vocalization were coded as no = 1, yes = 2 and treatment as: no pediment to foot = 1 and with lamb = 2. The data were previously standardized, with mean equal to zero and standard deviation equal to one and performed the analysis of main factors. A significant difference was observed for the single treatment (P = 0.0059). In the evaluation of the rotational factor loads of the reproductive behavior of females in the breeding period, it was observed that the variables, tail lift and tail flap (Principal Factor 1) were negatively associated, accounting for 26.71% of the accumulated variance. The smell action performed by the female associates negatively with the treatment creates at the foot (Main Factor 2), which explained 45.81% of the accumulated variance. Acceptance behavior of the male is negatively associated with urination (Principal Factor 3), being explained with 59.22% of accumulated variance. In the disinterest behavior it was observed that in the majority of the variables it creates to the foot and singles did not demonstrate this behavior (Main Factor 4).
Keywords: Cheirada; Estacionalidade; Lactação; Prostaglandina; Sincronização; Sniff; Seasonality; Lactation; Prostaglandin; Sync; CNPQ::CIENCIAS AGRARIAS